The MX/G/1 queue with queue length dependent service times. (2001) - Choi, Bong Dae; Kim, Yeong Cheol; Shin, Yang Woo; Pearce, Charles E. M.
Abstract : We deal with the M X / G / 1 queue where service times depend on the queue length at the service initiation. By using Markov renewal theory, we derive the queue length distribution at departure epochs. We also obtain the transient queue length distribution at time t and its limiting distribution and the virtual waiting time distribution. The numerical results for transient mean queue length and queue length distributions are given.